2002
DOI: 10.1097/00007632-200212150-00021
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Prediction Rule for Classifying Patients with Low Back Pain Who Demonstrate Short-Term Improvement With Spinal Manipulation

Abstract: It appears that patients with low back pain likely to respond to manipulation can be accurately identified before treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
504
5
19

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 574 publications
(543 citation statements)
references
References 60 publications
15
504
5
19
Order By: Relevance
“…The FABQW subscale has been previously correlated with work loss and disability in patients with chronic and acute LBP [10,22,37]. In our study FABQW cut-off point is 21, 2 points higher than previously reported in lumbar spine manipulation prediction study [6]. The difference may be associated with the chronicity of LBP.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations
“…The FABQW subscale has been previously correlated with work loss and disability in patients with chronic and acute LBP [10,22,37]. In our study FABQW cut-off point is 21, 2 points higher than previously reported in lumbar spine manipulation prediction study [6]. The difference may be associated with the chronicity of LBP.…”
Section: Discussioncontrasting
confidence: 41%
“…Further more, our criterion was also consistent with that adopted in a previous study [6] in which a more 'dramatic' intervention such as lumbar spine manipulation was examined.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The sacroiliac regional thrust manipulation technique has been shown to be effective at decreasing pain associated with hip dysfunction, low back pain, and SIJ dysfunction. 10,14,15,25,26 Hip anterior glide mobilizations/manipulations were performed when anterior glide hypomobility was perceived to be present, and hip posterior glide mobilizations/manipulations were performed when posterior glide hypomobility was perceived to be present. Any perceived lumbar segmental hypomobility was treated with grades III to IV central posterior-anterior mobilizations/manipulations.…”
Section: Sij and Hip Mobilization/manipulationmentioning
confidence: 99%